Marketing Habituation and Process Study of Online Food Industry ( A Study Case: Zomato) - Jelita Sparta; Shahad Alsumait; Apoorva Joshi (AIBPM Publisher, 2019)
Online food ordering platform has become the new habit which makes e-commerce sector, one of the essential part of our daily lives. This sector has changed the mindsets altogether; from people who are willing to stand in line for hours to get a great deal to get the food is now on the fingertips and that too at your doorstep. Basically, this paper focuses on the elaborative study about marketing strategy and operations used by Zomato to become the pioneer into the Online Food Service sector. Furthermore, this paper aims to have insights about the marketing habituation of a web-based business which influenced people to change the perception about food ordering and to study the aspect by which the organization managed the processes of this growing sector. This paper contains a case study on Zomato, the largest online food ordering platform in India. Zomato became a strong brand where its every order makes sure that the customer gets habituated for the service he receives. We will learn about the marketing tactics which Zomato has used exceptionally to establish into the market successfully. Keywords: marketing, habitual, Zomato, web business, online food delivery, e-commerce